Budaya Lokal dalam Perspektif Agama: Legitimasi Hukum Adat (‘Urf) Dalam Islam - Agung Setiyawan (UIN Sunan Kalijaga Yogyakarta, 2012)
Islam is a religion that has a universal characteristic, the worldview (Weltanschauung) of equality, justice, takaful, freedom and dignity as well as having a humanistic concept of theocentrism as core values of all the teachings of Islam. In terms of culture in society, Islam is letting local knowledge and local cultural products are productive and do not contaminate aqidah to exist, even putting traditional Islam as one of the basis for determining the law. As mentioned in one of the rules of jurisprudence thatsays